(untitled) (Bulletin of Innovative Research, 2026)
This article examines the historical, economic, political, and religious foundations of slavery in Central Asia during the 18th–19th centuries. The study analyzes the formation and development of slavery within the Bukhara Emirate, Khiva Khanate, and Kokand Khanate, focusing on the sources of the slave trade, the functioning of slave markets, and their connection with state policy. Particular attention is given to the role of religious fatwas in legitimizing slavery and to the use of the slave issue as a political instrument in diplomatic relations with Russia and Iran.